2021
DOI: 10.1097/01.aoa.0000744124.25473.ea
|View full text |Cite
|
Sign up to set email alerts
|

Uptrend in Distress and Psychiatric Symptomatology in Pregnant Women During the Coronavirus Disease 2019 Pandemic

Abstract: Introduction: Prenatal maternal distress has a negative impact on the course of pregnancy, fetal development, offspring development and later psychopathologies. The study aimed to determine the extent to which the Coronavirus disease 2019 (COVID-19) pandemic may aggravate pregnant women prenatal distress and psychiatric symptomatology. Material and methods: Two cohorts of pregnant volunteer women were evaluated, one that was recruited before the COVID-19 pandemic (n=496) through advertisements in prenatal clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
4
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 26 publications
3
44
4
10
Order By: Relevance
“…A longitudinal study comparing 102 pregnant women and a control group of 102 non-pregnant women showed a significant increase in depression and anxiety in parturients, and an increase in negative affects and a decrease in positive affects greater than in the control group (25). Another study of 1,754 pregnant women in Canada found that women recruited after the onset of the pandemic were almost twice as likely to report symptoms of depression, anxiety disorder, or substance use disorder (26). Finally, a subsequent meta-analysis of 23 studies involving 20,569 participants (16,797 pregnant women and 3,772 postpartum women) during the COVID-19 pandemic shows that 70% of patients present with psychological distress, 31% with depressive symptoms, and 49% with insomnia (24).…”
Section: Perinatal and Postpartum Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…A longitudinal study comparing 102 pregnant women and a control group of 102 non-pregnant women showed a significant increase in depression and anxiety in parturients, and an increase in negative affects and a decrease in positive affects greater than in the control group (25). Another study of 1,754 pregnant women in Canada found that women recruited after the onset of the pandemic were almost twice as likely to report symptoms of depression, anxiety disorder, or substance use disorder (26). Finally, a subsequent meta-analysis of 23 studies involving 20,569 participants (16,797 pregnant women and 3,772 postpartum women) during the COVID-19 pandemic shows that 70% of patients present with psychological distress, 31% with depressive symptoms, and 49% with insomnia (24).…”
Section: Perinatal and Postpartum Depressionmentioning
confidence: 99%
“…In a longitudinal single-arm cohort study conducted in China between May 1 and July 31, 2020 seventy-two pregnant patients with COVID-19 participated in follow-up surveys until 3 months after giving birth (57 cases) or having abortion (15 cases). All cases infected in the first trimester and 1/3 of cases infected in the second trimester had an abortion to terminate the pregnancy, and 22.2% of pregnant patients were suffering from post-traumatic stress disorder or depression at 3 months after delivery or induced abortion (26).…”
Section: Acute and Post-traumatic Perinatal Stress Disordermentioning
confidence: 99%
“…A study evaluating depression and anxiety symptoms' levels in the COVID-19 pandemic using two separate groups as pre-pandemic and pandemic groups reported that pregnant women during the COVID-19 pandemic had higher levels of stress, anxiety, and depression than pre-COVID-19 pregnant women 26 . This result was similar to the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…d Assessed at hospital discharge. mother and her fetus and the radical changes swiftly implemented in labor and birth care 35,[60][61][62][63][64][65][66][67][68][69][70][71] might explain this increase and its temporal trend.…”
Section: Discussionmentioning
confidence: 99%